2010
DOI: 10.1007/s00431-010-1324-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of propranolol as first-line treatment for infantile hemangiomas

Abstract: Our report supports the excellent effect and good tolerance of this novel therapy, and we propose the use of propranolol as first-line treatment for IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 18 publications
4
85
0
3
Order By: Relevance
“…15 Regardless of the mechanism of action, it is now indisputable that propranolol has an important effect on infantile hemangiomas, such that it causes their rapid regression. 16 Other groups have also reported similar results, 17,18 omas. 20 There is no recommended length of treatment, but it has been shown 20 that treating for a minimum of six months and at least until one year of age may prevent recurrences.…”
supporting
confidence: 53%
“…15 Regardless of the mechanism of action, it is now indisputable that propranolol has an important effect on infantile hemangiomas, such that it causes their rapid regression. 16 Other groups have also reported similar results, 17,18 omas. 20 There is no recommended length of treatment, but it has been shown 20 that treating for a minimum of six months and at least until one year of age may prevent recurrences.…”
supporting
confidence: 53%
“…7,[26][27][28][29] This relatively rapid onset of action for systemic therapy most likely encourages compliance. 30 In comparison, topical timolol maleate gel has been associated with growth arrest and a slower reduction in redness and thickness within the first 2 to 4 weeks of use as seen in 2 noncontrolled studies of the use of topical timolol maleate gel for IHs.…”
Section: Discussion Efficacymentioning
confidence: 99%
“…Propranolol, a well-tolerated, nonselective, β-AR blocker, has been recently reported to induce the involution of IHs (5), the most common tumor of infancy, efficiently and with good tolerance (15). Even though its mechanism of action has not been fully elucidated, recent research demonstrated that the expression of proangiogenic growth factors such as VEGF is downregulated by propranolol in a dose-dependent manner (6).…”
Section: Discussionmentioning
confidence: 99%